2009
DOI: 10.1007/s00216-009-3009-0
|View full text |Cite
|
Sign up to set email alerts
|

Melamine contamination

Abstract: In the summer of 2008, serious illnesses and deaths of babies in China were linked to melamine-tainted powdered infant formula. Melamine contains several metabolites, such as ammeline, ammelide, and cyanuric acid, and has been used for the adulteration of foods or milk to increase their apparent protein content. It is assumed that melamine and its metabolites are absorbed in the gastrointestinal tract, and precipitate in the kidney to form crystals. A new tolerable daily intake of 0.2 mg kg(-1) body weight was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
90
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(95 citation statements)
references
References 21 publications
1
90
0
3
Order By: Relevance
“…However, it was recently added to milk and various dairy products illegally due to its low cost and high nitrogen content (66% by mass), which can lead to incorrectly high readings for the apparent protein content when conventional standard tests are performed [2,3]. It has been reported that these high levels of melamine in milk killed thousands of pets [4] and caused renal function failure and even death in infants [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, it was recently added to milk and various dairy products illegally due to its low cost and high nitrogen content (66% by mass), which can lead to incorrectly high readings for the apparent protein content when conventional standard tests are performed [2,3]. It has been reported that these high levels of melamine in milk killed thousands of pets [4] and caused renal function failure and even death in infants [5].…”
Section: Introductionmentioning
confidence: 99%
“…Adulteration of melamine (2,4,6-triamino-1,3,5-triazine) in food is an important safety issue. In 2007, adulteration of pet food with melamine was the reason behind death of many pets (Tyan et al, 2009 (Kellicut et al, 2004). Further, it is also useful during intestinal surgery for prediction of ischemic regions of the intestine during surgery (Akbari et al, 2010) and for diagnosis of hemorrhagic shock (Cancio et al, 2006).…”
Section: Applications Of Hsi In Dairy Industrymentioning
confidence: 99%
“…Melamine (MM) (2, 4, 6-triamino-1, 3, 5-triazine) is an organic compound, a base with the chemical formula C 3 H 6 N 6 [1]. It can be hydrolyzed to ammeline (AMN), ammelide (AMD) and cyanuric acid (CA), which are by-products formed during MM synthesis (Fig.…”
Section: Introductionmentioning
confidence: 99%